Perceptions of Teachers and Students on the Adoption of Smartphones in EFL Learning in the Vocational School Context - Prasetyo, Anggitia Niken; Nurhadi, Kardi; Larasaty, Gina (English Education Department, Universitas Islam Indonesia, 2022)
With the shift from face-to-face learning to online mode, both teachers and students need to adjust the online learning due to the COVID-19 pandemic. During the pandemic, numerous researches has been undertaken, particularly ICT adoption in EFL learning. Despite a growing study investigating ICT use in the EFL context, relatively few studies report on the adoption of smartphones as a platform for teaching English situated in the vocational landscape. To fill this gap, this study is aimed to investigate teachers' and students' perceptions about the adoption of smartphones in EFL learning in one of Indonesia’s vocational schools. Grounded in a phenomenological case study, this research provided details of vocational English teachers' and students’ live experiences interacting in English teaching via smartphone as a learning platform. In this study, two English teachers and three students have recruited as the participants voluntarily. The result of this study showed numerous benefits and challenges in the use of smartphones in the vocational school context. The writer found that the adoption of smartphones is beneficial, helpful, practical, and enjoyable for learning English, especially in using several smartphone applications. Despite the benefits of a smartphone, the participants reported that the instructions need to explain clearly as they are sometimes confused with the teacher's instructions. Drawing on the findings, this research implied that English teachers are suggested to adopt a wide range of learning resources to gain better students' understanding of learning English.